A localized adaptive architecture for dynamic wireless sensor networks - Hussain, Sajjd; Ahmed, Muntasir; Joy, Kishanu Roy; Hasan, Md. Mehedi (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.